“Sarmatism” as a Fluid Concept - Tauer, Sebastian (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
Reviev: Maciej Nawrocki, „Sarmatyzm”. Historia pojęcia, Wydawnictwo Naukowe UMK, Toruń 2025.